Foreign Capital and Economic Growth: A Social Network Analysis, 2001–2017. (June 2022) - Clark, Rob; Kentor, Jeffrey
Foreign direct investment (FDI) holds a substantial and rapidly growing presence across every region of the world. However, our understanding of how foreign capital impacts economic growth in receiving and investing countries remains in question, despite nearly five decades of research. Our study contributes to this long-standing debate by (1) applying social network analysis to the FDI-growth literature, (2) utilizing recently available bilateral data for a global sample of countries during the post-2000 period, and (3) examining the impact of both inward and outward foreign capital on economic growth. While conventional measures of FDI typically focus on investment volume, we argue that the network structure of investment relations may be equally—or more—important. We construct a global network of FDI during the 2001–2017 period, bringing together two data sets: (1) the United Nations Conference on Trade and Development's Bilateral FDI Statistics, and (2) the International Monetary Fund's Coordinated Direct Investment Survey . We then calculate network centrality scores that reflect each country's level of inward and outward embeddedness in the global FDI network. Drawing from a sample of 1, 467 observations across 137 countries during the 2001–2017 period, we estimate two-way fixed effects models to examine the effect of FDI centrality on economic growth. Net of other predictors, we find that inward and outward centrality are positively—and independently—associated with growth, while more conventional measures of foreign capital display weaker and inconsistent effects.